Análisis e identificación de las organizaciones de la economía popular y solidaria en la Parroquia Malacatos, cantón Loja - Ochoa Pesantes, Jorge Vinicio (2018)
The popular and solidary economy is the form of economic organization, where its members, individually or collectively, organize and develop processes of production, exchange, marketing, financing and consumption of goods and services. In our country the Popular and Solidarity Economy, is structured in three sectors: Cooperative sector, associative sector, community sector and popular economic units. However, in the sector of the Popular and Solidarity Economy, exclusion, marginality and economic structures continue to exist that contradict the constitutional concept of Good Living. In this context, the present thesis entitled "Analysis and identification of the Popular and Solidarity Economy organizations in the Malacatos parish, canton Loja." Was carried out in order to contribute to the development of the Popular and Solidarity Economic Sector, in this way the main objective was to evaluate the forms of cooperation and solidarity that coexist in the framework of the Popular and Solidarity Economy, in order to know the influence of these new forms of economy, the specific objectives are focused on characterizing the socioeconomic aspects, diagnose the intervention of financial institutions of the popular and solidarity economy and measure their impact in the study area, with this information formulate a financial proposal with solidarity values and territorial relevance. For the characterization of socio-economic aspects in the Malacatos parish, direct observation cards were used to collect information from the National Plan for Development and Territorial Planning (PDyOT), which allowed to know in a general way the reality of this parish, through the study of field was located seven associations and productive companies, fifteen water boards of which ten of them are merged into a single board called channel irrigation system Malacatos campaign, five social assistance associations, twenty sports clubs, three cultural groups and two associations of citizen participation, likewise found three financial institutions which offer their products and services in the parish, it should be noted 5 that for the present study is considered productive associations and financial organizations. Regarding the second objective, the diagnosis and intervention of the financial institutions of the popular and solidarity economy and measure its impact in the study area, was carried out through an interview applied to the managers of financial organizations, and a survey aimed at the partners or clients of these organizations, a cause-effect matrix to measure the impact, having as a result that financial institutions have contributed significantly to improving the quality of life of people, maintaining a high positive impact on the economic and social components . In the economic component, the main activity is the microcredit granted by financial institutions, which range from 100 to 16,000.00 dollars, which has allowed the population of Malacatos to generate new sources of employment, increase productivity and improve the level of income of families, in the social component microcredit activities have allowed to improve the quality of life of the population through financing for production, seeking the common good of families and promoting the education of their children. The last objective was the elaboration of a proposal for an alliance of the popular and solidarity economy actors to boost productivity in the Malacatos parish, aimed at associations of the Popular and Solidarity Economy, which proposed a series of group activities that they will allow the integration of these actors and thus increase the economic-social and productive development of the population, generating new ventures and new sources of employment, which are fundamental for the progress of the parish.